THE ROLE OF CROWDFUNDING BASED DONATION MECHANISM IN AL-QUR’AN EDUCATION DEVELOPMENT - Uci Wulansari; Achsania Hendratmi (Airlangga Journal of Innovation Management, 2021)
Crowdfunding mechanism in fundraising activities has experienced rapid development these recent years in various parts of the world. This requires philanthropic institutions to make digital innovations in their fundraising activities. This study aims to determine the role of crowdfunding-based donation mechanism in the advancement of Al-Qur'an education with a case study of tabungamal.id platform. The research method used is a qualitative approach with an explanatory case study method. Data collection techniques using direct interviews and observation. The mechanism of tabungamal.id was identified based on crowdfunding intermediaries function proposed by Philipp Haas et al, namely lot size transformation, risk transformation, and information transformation. The results of this study indicate that crowdfunding-based donation mechanism at tabungamal.id has roles in advancing Al-Qur'an education, including reducing education disparities between economic classes and regions, supporting innovation in Al-Qur'an learning, and increasing community participation in advancement of Al-Qur'an education. These findings can be implemented by Islamic philanthropic institutions in developing a crowdfunding-based donation mechanism to optimize role of Islamic philanthropic institutions in digital era.